Summary of the Chain Rule

Essential Concepts

  • The chain rule allows us to differentiate compositions of two or more functions. It states that for h(x)=f(g(x))h(x)=f(g(x)),
    h(x)=f(g(x))g(x)h(x)=f(g(x))g(x)
    • In Leibniz’s notation this rule takes the form
      dydx=dydududxdydx=dydududx
  • We can use the chain rule with other rules that we have learned, and we can derive formulas for some of them.
  • The chain rule combines with the power rule to form a new rule:
    If h(x)=(g(x))nh(x)=(g(x))n, then h(x)=n(g(x))n1g(x)h(x)=n(g(x))n1g(x)
  • When applied to the composition of three functions, the chain rule can be expressed as follows: If h(x)=f(g(k(x)))h(x)=f(g(k(x))), then h(x)=f(g(k(x)))g(k(x))k(x)h(x)=f(g(k(x)))g(k(x))k(x)

Key Equations

  • The chain rule
    ddx(f(g(x)))=f(g(x))g(x)ddx(f(g(x)))=f(g(x))g(x)
  • The power rule for functions
    ddx((g(x)n)=n(g(x))n1g(x)ddx((g(x)n)=n(g(x))n1g(x)

Glossary

chain rule
the chain rule defines the derivative of a composite function as the derivative of the outer function evaluated at the inner function times the derivative of the inner function